2014
DOI: 10.1063/1.4904303
|View full text |Cite
|
Sign up to set email alerts
|

Full kinetic simulations of plasma flow interactions with meso- and microscale magnetic dipoles

Abstract: We examined the plasma flow response to meso-and microscale magnetic dipoles by performing three-dimensional full particle-in-cell simulations. We particularly focused on the formation of a magnetosphere and its dependence on the intensity of the magnetic moment. The size of a magnetic dipole immersed in a plasma flow can be characterized by a distance L from the dipole center to the position where the pressure of the local magnetic field becomes equal to the dynamic pressure of the plasma flow under the magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…From the equatorial plane, we can clearly see that the maximum electron density located inside the dipole, is close to the back dipole center. This spiral distribution mainly attribute to the gyration of electron [1]. The stretching of the tail is visible from the elongated blue region along x direction, which is consistent with the development stage in Figure 2.…”
Section: The Formation Of a Magnetospheresupporting
confidence: 84%
See 1 more Smart Citation
“…From the equatorial plane, we can clearly see that the maximum electron density located inside the dipole, is close to the back dipole center. This spiral distribution mainly attribute to the gyration of electron [1]. The stretching of the tail is visible from the elongated blue region along x direction, which is consistent with the development stage in Figure 2.…”
Section: The Formation Of a Magnetospheresupporting
confidence: 84%
“…Several simulations of magnetosphere using explicit PIC codes are reported in Refs. [3,8,4,1]. We developed a new relativistic particle mover with adaptive sub-cycling to resolve in time the fast gyration of particles located in strong dipolar magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this work showed not only that non-Maxwellian particle distributions are generated from the interaction with the mini magnetosphere, but also that the plasma deflection occurs due to microscopic collective electric fields associated with charge separation between electrons and ions, which can only be appropriately captured using PIC simulations. Ashida et al 28 studied the interaction between an unmagnetized plasma flow and magnetic obstacles with sub-Larmor radius magnetic obstacles, showing that mini magnetospheres can be formed even for obstacles sizes smaller than the ion gyroradius. Other recent works 14,29 with full PIC simulations show that enhanced proton flux around lunar magnetic anomalies can be responsible for the appearance of dark lanes on lunar swirls, regions on the lunar surface commonly found around mini magnetospheres that receive enhanced ageing from direct interaction with the solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from observations, several attempts have been made to model the solar wind plasma interaction with lunar magnetic anomalies theoretically, numerically, and experimentally using single dipole [ Siscoe and Goldstein , ; Harnett and Winglee , , ; Poppe et al , ; Kallio et al , ; Wang et al , , ; Shaikhislamov et al , ; Jarvinen et al , ; Deca et al , ; Ashida et al , ] and multidipole [ Harnett and Winglee , ] approximations. Generally, these models, consistent with observations, have shown that strong magnetic anomalies may shield the lunar surface from solar wind and have a direct impact on surface weathering and swirl albedo markings [ Blewett et al , ; Poppe et al , ].…”
Section: Introductionmentioning
confidence: 99%